Synthesis of Vertically Aligned Carbon Nanotubes on Silicalite-1 Monolayer-Supported Substrate. (9th February 2014) - Zhao, Wei; Basnet, Bijay; Kim, Sukyoung; Kim, Ik Jin
Abstract : Monodisperse magnetic F e 3 O 4 nanoparticles (NPs) with the size of ca. 3.5 nm were prepared and used as the catalysts for the synthesis of vertically aligned carbon nanotube (VACNT) arrays. A silicalite-1 microcrystal monolayer was used as the support layer between catalyst NPs and the silicon substrate. Compared to our previous report which used radio-frequency- (rf-) sputtered F e 2 O 3 film as the catalyst, F e 3 O 4 NPs that were synthesized by wet chemical method showed an improved catalytic ability with less agglomeration. The silicalite-1 crystal monolayer acted as an effective "buffer" layer to prevent the catalyst NPs from agglomerating during the reaction process. It is believed that this is the first report that realizes the vertical alignment of CNTs over the zeolite monolayer, namely, silicalite-1 microcrystal monolayer, instead of using the intermediate anodic aluminum oxide (AAO) scaffold to regulate the growth direction of CNT products.